Sportomics in professional soccer players: metabolomics results during preseason - Pintus, R.; Bongiovanni, T.; Corbu, S.; Francavilla, V. C.; Dessí, A.; Noto, A.; Corsello, G.; Finco, G.; Fanos, V.; Marincola, F. C. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Sportomics is the application of metabolomics to study the metabolism shifts of individuals that practice sports or do physical exercise. This aim was reached by the analysis of low molecular weight metabolites (<1.5 kDa) present in biological fluids such as blood, saliva or urine. METHODS: In this study, authors performed a 1H-NMR analysis of urine from 21 professional soccer players collected at 3 different time points during the preseason preparation period before the beginning of Serie A Championship (first division) in Italy. RESULTS: Urine profile changed during the observational period. In particular, significant variations were observed for trimethylamine-N-oxide, dimethylamine, hippuric acid, hypoxanthine, guanidoacetic acid, 3-hydroxybutyric acid, citric acid and creatine. These modifications could be related to the diet, training and microbiota. For instance, trimethylamine-N-oxide and hippuric acid are both of dietary origins but are also related to the microbiota, while 3-hydroxy-butyric acid is associated with the type of physical exercise. CONCLUSIONS: This is the first sportomics study ever performed on professional soccer players, according to authors` knowledge. In the future, sportomics could be applied in a tailored way to choose the best diet and training program in the single individual to obtain the best possible performances and to prevent injuries of athletes.